THE CONCEPT OF IMPROVING THE DESIGN OF THE TRACK - Zhelnin, H. H.; Lysiuk, V. S.; Kuznietsov, V. V. (Science and Transport Progress, 2003)
In article the basic directions of perfection of a design of a railway in modern conditions of operation are recommended.